The role of CARDPC in response to COVID-19 in primary care in China (2020)
OVID-19 is wreaking havoc around the world, which is a serious challenge to all our health systems. China reacted quickly in the early stage of the pandemic, and accumulated a lot of experiences, especially in the prevention and control of COVID-19 at the primary care level. Here, we would like to share how the Chinese Alliance for Respiratory Diseases in Primary Care (CARDPC) played a role in the pandemic, hoping to provide guidance and hope for effective control of the outbreak worldwide, for future public health emergencies and for systematic management of chronic respiratory diseases in the community.